2021
DOI: 10.3389/ffgc.2020.601046
|View full text |Cite
|
Sign up to set email alerts
|

Springtime Drought Shifts Carbon Partitioning of Recent Photosynthates in 10-Year Old Picea mariana Trees, Causing Restricted Canopy Development

Abstract: Springtime bud-break and shoot development induces substantial carbon (C) costs in trees. Drought stress during shoot development can impede C uptake and translocation. This is therefore a channel through which water shortage can lead to restricted shoot expansion and physiological capacity, which in turn may impact annual canopy C uptake. We studied effects of drought and re-hydration on early season shoot development, C uptake and partitioning in five individual 10-year old Picea mariana [black spruce] trees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 74 publications
2
5
0
Order By: Relevance
“…Furthermore, results from δ 13 C measurement showed that the fraction of new C decreased with the needle age (Y0 > Y2 > Y4; Fig. 7), indicating that recent photosynthates were strongly invested in structural compounds to build Y0 needle biomass, as also reported for young spruce needles (Schadel et al, 2009;Jensen et al, 2021), as opposed to allocation to metabolic storage compounds in existing older cohorts. We therefore expected to observe a large amount of newly assimilated carbon (80-90%) in the Y0 needles considering their active metabolic stage (Sachse et al, 2015;Jensen et al, 2021).…”
Section: Carbon Assimilation and Allocation In Perennial Needle Cohortssupporting
confidence: 56%
See 4 more Smart Citations
“…Furthermore, results from δ 13 C measurement showed that the fraction of new C decreased with the needle age (Y0 > Y2 > Y4; Fig. 7), indicating that recent photosynthates were strongly invested in structural compounds to build Y0 needle biomass, as also reported for young spruce needles (Schadel et al, 2009;Jensen et al, 2021), as opposed to allocation to metabolic storage compounds in existing older cohorts. We therefore expected to observe a large amount of newly assimilated carbon (80-90%) in the Y0 needles considering their active metabolic stage (Sachse et al, 2015;Jensen et al, 2021).…”
Section: Carbon Assimilation and Allocation In Perennial Needle Cohortssupporting
confidence: 56%
“…7), indicating that recent photosynthates were strongly invested in structural compounds to build Y0 needle biomass, as also reported for young spruce needles (Schadel et al, 2009;Jensen et al, 2021), as opposed to allocation to metabolic storage compounds in existing older cohorts. We therefore expected to observe a large amount of newly assimilated carbon (80-90%) in the Y0 needles considering their active metabolic stage (Sachse et al, 2015;Jensen et al, 2021). Surprisingly, our results show lower fractions of newly assimilated C in the Y0 needles which increased with warming and maximized at 70% (in plant tissues and cuticular lipids; Fig.…”
Section: Carbon Assimilation and Allocation In Perennial Needle Cohortssupporting
confidence: 55%
See 3 more Smart Citations